Prevention of vision loss protects against age-related impairment in learning and memory performance in DBA/2J mice - Wong, Aimee; Brown, Richard (Frontiers in Aging Neuroscience, 2013)
The DBA/2J mouse is a model of pigmentary glaucoma in humans as it shows age‐related increases in intraocular pressure, retinal ganglion cell death and visual impairment. Previously, we showed that visual ability declines from 9 ‐12 months of age and visual impairment is correlated with poor learning and memory performance in visuo‐spatial tasks but not in tasks that do not depend on visual cues. To test the “sensory impairment” hypothesis of aging, which postulates that sensory impaired individuals are disadvantaged in their performance on psychometric tests as a direct result of difficulties in sensory perception, we treated DBA/2J mice with a conventional glaucoma medication used in humans (Timoptic‐XE, 0.00, 0.25 or 0.50%) daily from 9 weeks to 12 months of age to determine whether prevention of vision loss prevented the decline in visuo-spatial learning and memory performance. At all ages tested (3, 6, 9 and 12 months of age), mice treated with Timoptic-XE (0.25 and 0.50%) maintained a high level of performance, while 12 month old control mice (0.00%) exhibited impaired performance in visually‐dependent, but not non‐visual tasks. These results demonstrate that when sensory function is preserved, cognitive performance is normalized. Thus, as in many aging humans, DBA/2J mice show age-related decrements in performance on visually presented cognitive tests, not because of cognitive impairment but as a direct consequence of poor visual ability. Our results demonstrate that age-related impairment in performance in visuo-spatial tasks in DBA/2J mice can be prevented by the preservation of visual ability.